1993
DOI: 10.1073/pnas.90.2.770
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 null mutation in mice causes excessive inflammatory response and early death.

Abstract: To delineate specific developmental roles of transforming growth factor fPI (TGF-P1) we Five distinct TGF-P3 genes have been identified in vertebrates and three of these (TGF-f31, TGF-p2, and TGF-(33) are expressed in mammals. Each of the three isoforms has been highly conserved throughout evolution, suggesting specific roles for each (1, 2). These three isoforms share a high degree of amino acid sequence homology in the mature domain, are often coexpressed and colocalized, and have qualitatively similar act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
1,237
5
8

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,754 publications
(1,276 citation statements)
references
References 30 publications
26
1,237
5
8
Order By: Relevance
“…TGF-b plays a critical role in collagen formation and extracellular matrix deposition in addition to its role in down-regulating T cell responses [5]. Consequently, TGF-b -/-mice exhibit approximately 50% embryonic lethality and live-born TGF-b -/-mice develop multiorgan inflammation, primarily in the heart and lung, and die within 2-3 weeks of birth [7]. The early lethality of TGF-b -/-mice makes this an unsuitable model in which to study infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-b plays a critical role in collagen formation and extracellular matrix deposition in addition to its role in down-regulating T cell responses [5]. Consequently, TGF-b -/-mice exhibit approximately 50% embryonic lethality and live-born TGF-b -/-mice develop multiorgan inflammation, primarily in the heart and lung, and die within 2-3 weeks of birth [7]. The early lethality of TGF-b -/-mice makes this an unsuitable model in which to study infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we investigated whether expression of the neutralizing ligand trap could blunt TGF-b-induced expression of these two factors. Vector control (VC) or Fc:TbRII(ECD)-expressing MDA-MB-231 breast cancer cells were allowed to condition serum free media for 48 h and subsequently incubated in the absence or presence of TGF-b1 for a further 3 h. Quantitative Loss or reduction of TGF-b1 levels in host-derived tissue prevents the efficient establishment of breast cancer cells in bone To specifically interrogate the importance of bonederived TGF-b1 on the ability of breast cancer cells to form osteolytic lesions, we used TGF-b1-deficient mice that were bred onto a RAG2-deficient background (Engle et al, 1999), which rescues the early lethality observed in TGF-b1-null mice due to widespread inflammatory disease (Shull et al, 1992;Kulkarni et al, 1993). To ensure that the RAG2À/À mice permitted xenografting of human breast cancer cells, we injected an MDA-MB-231 variant that aggressively metastasizes to bone (1833-TR cells) into mammary fat pads of RAG2À/À mice (Kang et al, 2003;Minn et al, 2005).…”
Section: Tgf-b-neutralizing Ligand Trap Impairs Signaling Induced Bymentioning
confidence: 99%
“…TGF-b1 is a potently suppressive cytokine that plays a critical role in the regulation of immune function, as illustrated by the development of a severe autoimmunelike syndrome in TGF-b1 -/-mice [11,12]. Genetic disruption of TGF-b signaling in T cells by overexpression of a dominant-negative TGF-b type II receptor (DNRIITg), conditional deletion of the TGF-b type II receptor, or inactivation of the gene encoding Smad3, alters the sensitivity of T cells to the inhibitory effects of TGF-b and leads to aberrant T cell responses [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…While CD4 + CD25 + Treg cells from IL-4 -/-and IL-10 -/-mice are as effective as WT CD4 + CD25 + T cells in mediating suppression of AIG, CD4 + CD25 + Treg cells from IL-10 -/-mice cannot control IBD induced by antigen-experienced effector T cells [8,9]. Similarly, IL-10 -/-CD4 + CD25 + Treg cells, in contrast to WT cells, fail to attenuate effector T cell responses to Leishmania major in resistant C57BL/6 mice [10].TGF-b1 is a potently suppressive cytokine that plays a critical role in the regulation of immune function, as illustrated by the development of a severe autoimmunelike syndrome in TGF-b1 -/-mice [11,12]. Genetic disruption of TGF-b signaling in T cells by overexpression of a dominant-negative TGF-b type II receptor (DNRIITg), conditional deletion of the TGF-b type II receptor, or inactivation of the gene encoding Smad3, alters the sensitivity of T cells to the inhibitory effects of TGF-b and leads to aberrant T cell responses [13][14][15].…”
mentioning
confidence: 99%
See 1 more Smart Citation